Timber Buildings and Sustainability - Concu, Giovanna (IntechOpen, 2019)
The construction sector alone accounts for 40 percent of resource consumption and environmental pollution. In line with the current considerations on environmental sustainability, particular attention is paid to eco-sustainable building materials such as timber. Timber is able to perform both load-bearing and comfort constructive functions. It is also a natural, renewable and recyclable material. However, its use as an engineering material calls for constant development and research. This book provides insight into the spread of the use of timber in the construction industry, presenting some thoughts on important aspects related to production, design and responsible use.